2020
DOI: 10.1101/2020.06.16.126631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The sensorimotor strategies and neuronal representations of tactile shape discrimination in mice

Abstract: 14Humans and other animals can identify objects by active touch, requiring the coordination of exploratory 15 motion and tactile sensation. The brain integrates movements with the resulting tactile signals to form a 16 holistic representation of object identity. We developed a shape discrimination task that challenged head-17 fixed mice to discriminate concave from convex shapes. Behavioral decoding revealed that mice did this 18 by comparing contacts across whiskers. In contrast, mice performing a shape detec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 173 publications
(202 reference statements)
1
8
0
Order By: Relevance
“…4c). In agreement with [8], we also found a deviation from classic somatotopy: C1 contacts were more strongly represented than C2 contacts in the C2 column, and than C3 contacts in the C3 column ( Supplementary Fig. S7).…”
Section: C3supporting
confidence: 88%
See 2 more Smart Citations
“…4c). In agreement with [8], we also found a deviation from classic somatotopy: C1 contacts were more strongly represented than C2 contacts in the C2 column, and than C3 contacts in the C3 column ( Supplementary Fig. S7).…”
Section: C3supporting
confidence: 88%
“…At response time shape category could be decoded with a performance of 56.8% ± 1.7% (green) and the animal's choice with a performance of 65.4% ± 2.0% (blue). Both shape and choice could be reliably decoded from neuronal ensembles in which we grouped together the activity from different recording sessions (pseudopopulations) [8]. As expected, populations of barrel cortex neurons encoded information about whisker contacts ( Fig.…”
Section: Nonlinear Mixed Selectivity In the Mouse Barrel Cortexmentioning
confidence: 63%
See 1 more Smart Citation
“…Research into many sensory modalities, especially somatosensation, has probed cortical circuitry and function using detection paradigms, in which animals must report the presence or absence of a stimulus (Brecht et al 1997, Hutson & Masterton 1986. Neurons in S1 have activity that correlates with touch, and manipulating their activity can alter detection behavior (Guo et al 2014b, Miyashita & Feldman 2013, O'Connor et al 2010, Sachidhanandam et al 2013, Yu et al 2016). Yet we recently showed that barrel cortex is, surprisingly, dispensable for both performing and learning a whisker-based go/no-go object detection task (Hong et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mice, rats and some other small rodents and insectivores can move their large facial whiskers rhythmically with frequencies of 5–20 Hz, occasionally up to around 30 Hz, a speed that is rather unique in mammals (Berg and Kleinfeld, 2003 ; Knutsen et al, 2006 ; Munz et al, 2010 ; Rahmati et al, 2014 ). In doing so, they can actively explore their environment and establish the shapes and textures of the objects around them (Rodgers et al, 2020 ). Neural interpretation of such active touch is computationally demanding and consequently a large part of the rodent brain is related to the whisker system (Kleinfeld et al, 1999 ; Bosman et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%